Pemberdayaan Usaha Kecil Donat Sanders di Desa Sariwangi, Kecamatan Parongpong, Kabupaten Bandung Barat - Dinihayati, Erti; Purwanti, Yanti (Jurnal Bisnis Indonesia, 2024)
West Bandung Regency is one of the areas in West Java which has abundant natural resources. One ofthe natural resources owned is the culinary field. Various products are produced, in almost severalareas in West Bandung Regency most of them process various kinds of culinary products. Most of theproducts produced are in the form of food. The problems faced by business actors are related toentrepreneurship, information technology and the application of technology products where businessactors experience problems in terms of information technology. In addition, the problems faced bybusiness actors are related to the understanding of information technology in the field of marketing.Where business actors have limited resources, including manpower and budget, making it difficult toallocate sufficient time and effort to consistently update social media as a marketing medium. Inconnection with the problems faced by business actors, the solution taken is to increase understandingof business actors related to entrepreneurship, information technology and marketing. Theimplementation method used to overcome the problems faced by business actors is through trainingand guidance. The training is carried out by giving lectures and understanding related toentrepreneurship, information technology and marketing. Guidance is given in the form of directpractice and continued with the provision of understanding until finally they can be independent. Inaddition, the provision of production raw material assistance to partners.Keywords: Empowerment of Culinary Products; Enterpreuner